Effects of prenatal exposure to deltamethrin on forced swimming behavior, motor activity, and striatal dopamine levels in male and female rats - Lazarini, C. A.; Florio, J. C.; Lemonica, I. P.; Bernardi, M. M. (Elsevier B.V., 2001)
The effects of prenatal exposure of rat pups to 0.08 mg/kg deltamethrin (DTM) on physical, reflex and behavioral developmental parameters, on forced swimming and open-field behaviors, and on striatal monoamine levels at 60 days of age were observed. Maternal and offspring body weight, physical and reflex development were unaffected by the exposure to the pesticide. At 21 days of age, open-field locomotion frequency and immobility duration of male and female offspring were not different between control and exposed animals. However, male rearing frequency was increased in experimental animals. A decreased immobility latency to float and in general activity after the swimming test in male offspring was observed at adult age; no interference was detected in the float duration during the swimming test. In addition, these animals presented higher striatal 3,4-dihydroxyphenylacetic acid (DOPAC) levels without modification in dopamine (DA) levels and an increased DOPAC/DA ratio. These data indicate a higher activity of the dopaminergic system in these animals. Noradrenaline (NA) levels were increased, while MHPG levels were not detectable in the system studied. Serotonin (5-HT) and 5-hydroxyindolacetic acid (5-HIAA) levels, as well as the homovanillic acid (HVA)/DA ratio, were not modified by the exposure to the pesticide. No changes were observed in swimming and open-field behaviors nor were there any changes in striatal monoamines or their metabolites in the female experimental group. In relation to the pesticide formula, the present data showing that prenatal exposure to DTM alters latency to float and the activity of striatal dopaminergic system might reflect a persistent effect of the pesticide on animal motor activity, mainly in males. on the other hand, the decrease in general activity observed in experimental male rats suggests higher levels of emotionality induced by previous exposure to the swimming behavior test in relation to control animals. Data gathered in the present study may be important for the assessment of the safety of pyrethroid insecticides. (C) 2001 Elsevier B.V. All rights reserved.